The impact of user preference and perceived value on customer satisfaction and marketability at traditional handicraft product - Haoran Liu; Hassan Alli; Irwan Syah Md Yusoff (Cogent Business & Management, 2024)
The main objective of this study is to investigate the impact of user preferences and perceived value on traditional handicraft products in terms of customer satisfaction and sales performance through empirical research. The study used a questionnaire to collect data from 299 customers in retail shops of handicraft products in Yunnan Province, China, and used PLS-SEM (Partial Least Squares Structural Equation Modelling) as well as Smart PLS software to analyse the data. The results of the study clearly show that user preferences have a significant positive impact on customer satisfaction, sales performance, and perceived value. Moreover, perceived value was also found to have a positive impact on customer satisfaction and sales performance. In addition, the findings reveal that customer satisfaction has a positive impact on sales performance. Based on these findings, this study further discusses the potential impact on managers.
Keywords: 650; User preference; perceived value; customer satisfaction; marketability; traditional handicraft product; PLS-SEM